The sources and transport pathways of sediment in the northern Ninety-east Ridge of the India Ocean over the last 35000 years - Cai, Zhourong; Huang, Qianru; Yin, Zhengxin; Huang, Xiaofeng; Chen, Liang; Tang, Meng (Frontiers in Marine Science, 2023)
The Ninety-east Ridge (NER) is located in the southern Bay of Bengal in the northeast Indian Ocean and is composed of pelagic and hemipelagic sediments. In addition to contributions from marine biomass, the ridge also contains terrestrially sourced sedimentary material. However, considerable disagreement remains regarding the origin of these terrestrial materials and transport pathways. This paper discusses the collection of seafloor surface sediments and three sediment cores recovered from the northern region of the NER, as well as the analysis of clay minerals, Sr-Nd isotopes, and sediment grain size. The ages of the three core sediments are constrained by AMS 14C dating to better establish the source and transport pathways of the terrestrial materials within NER sediments over the past 35000 years. The research results show that the Qinghai-Tibet Plateau is the predominate source of terrigenous sedimentary material in the NER. In the plateau, the crustal materials were weathered and stripped and then transported to the Andaman Sea via the Irrawaddy River. From there, the material was transported westward by monsoon-driven circulation to the northernmost part of the NER before being transported to the south for final deposition. This transport mode has changed little over the past 35000 years. However, during the rapidly changing climate of the Younger Dryas (12.9~11.5 ka BP), there were some variations in the input amount, grain size, and Sr-Nd isotope value of the source material. The above conclusions are significant for re-evaluating the source of terrigenous sediments, the temporal and spatial changes in transport modes, and the sensitivity of the NER to climatic shifts.